Identifikasi Mineral Pembawa Hara untuk Menilai Potensi Kesuburan Tanah - Indriyani Bali; Asmita Ahmad; Christianto Lopulisa (Jurnal Ecosolum, 2018)
Soil minerals are very important for plants and can be use to assess the potential of soil fertility. This study aims to assess the potential of soil fertility based on mineral identification in Banggae and Eastern Banggae Subdistrict, Majene District, West Sulawesi Province. The method used in this research is descriptive quantitative, by identifying the minerals in the parent material and soil from thin section using polarizing microscope, quantification method for minerals percentage, and classified of nutrient potential with percentage of mineral content reduced by the percentage content of the quartz. The results showed that the dominant mineral found in the parent material and soil are pyroxene, plagioclase, hornblende, biotite, calcite, quartz and opaque, but the size of mineral are smaller than in the parent material. Potential of nutrients generated in the form of weatherable minerals are biotite, calcite, plagioclase, hornblende and pyroxene containing elements such as Mg, Ca, K, Fe and Na. Potential soil fertility in parent material currently on the moderate criteria (48% to 70%), while on the soil with middle criteria (48% to 70%) in P1L1, P2L1, P4L1, P8L1, P9L1, P10L1, P11L1 and P11L2 and good criteria (73% to 79%) in P3L1, P3L2, P4L2, P5L1, P5L2, P6L1, P7L1 and P9L2. Potential nutrient contained in the mineral is not available for plants, because it has not been supported by external factors such as the low availability of water. This is due to the climate condition especially rainfall in research area is in the range of 949.0 to 2557.1 mm/year with an average annual rainfall of 1608.0 mm/year.